Artificial neural network - Muhamad Nor, Norfarina; Yahya, Mohamad Ridzuan; Saad, Wan Zuhainis; Mohamad, Rosfarizan (Universiti Putra Malaysia Press, 2016)
A biological neurone receives inputs from many sources, combines and presents them as a non-linear operation before releasing outputs as the final result. Inspired by the neural structures of human brain. Artificial Neural Network (ANN) is a computational model for process optimization that has an ability to recognize and reproduce the networks via training of various input-output systems that lead to the demonstration of complex systems.